Expanding the mutational spectrum of congenital microcephaly in Pakistani families - Farooq, Sundas; Asif, Maria; Abbasi, Ansar A.; Latif, Zahid; Ku, Bonsu; Makhdoom, Ehtisham Ul Haq; Shadab, Madiha; Khan, Muzammil Ahmad; Muzammal, Muhammad; Waqar, Raja; Nisar, Rameez; Khan, Falak Sher; et al. (Frontiers in Genetics, 2026)
Autosomal recessive primary microcephaly (MCPH) is a genetically heterogeneous neurodevelopmental disorder characterized by a markedly reduced head circumference (−3 to −5 standard deviations) at birth, with relatively preserved brain architecture. Affected individuals often present with mild to moderate intellectual disability, and the condition is more prevalent in populations with high rates of consanguinity, such as Pakistan. To date, pathogenic variants in at least 32 genes have been associated with MCPH, with ASPM and WDR62 accounting for the majority of cases (68% and 14%, respectively). In this study, we investigated four consanguineous families with congenital microcephaly and identified three novel variants in CPAP, WDR62, and ASPM. In Family 1, we identified a novel missense variant (c.3947C>A; p. (Thr1316Lys) in CPAP (NM_018451.4) located within the highly conserved TCP domain, which mediates interactions with other MCPH proteins, including STIL and CEP135. Family 2 harbored a previously unreported splice-site variant, c.2867 + 5G>T, in WDR62 (NM_001083961.2). In Families 3 and 4, we identified one novel (c.3188T>G; p. (Leu1063*)) and one previously reported (c.9730C>T; p. (Arg3244*)) pathogenic variant in ASPM (NM_018136.4). Computational analyses and structural modeling indicated that all these variants are likely deleterious, disrupting normal protein function. Our findings expand the mutational spectrum of CPAP and WDR62 and reinforce ASPM as the most frequently mutated gene underlying MCPH in the Pakistani population.